Concise Review: Defining and Targeting Myeloma Stem Cell‐Like Cells. (May 2014) - Abe, Masahiro; Harada, Takeshi; Matsumoto, Toshio
Abstract Multiple myeloma (MM) remains incurable despite recent advances in the treatment of MM. Although the idea of MM cancer stem cells (CSCs) has been proposed for the drug resistance in MM, MM CSCs have not been properly defined yet. Besides clonotypic B cells, phenotypically distinct MM plasma cell fractions have been demonstrated to possess a clonogenic capacity, leading to long‐lasting controversies regarding the cells of origin in MM or MM‐initiating cells. However, MM CSCs may not be a static population and survive as phenotypically and functionally different cell types via the transition between stem‐like and non‐stem‐like states in local microenvironments, as observed in other types of cancers. Targeting MM CSCs is clinically relevant, and different approaches have been suggested to target molecular, metabolic and epigenetic signatures, and the self‐renewal signaling characteristic of MM CSC‐like cells. Stem Cells2014;32:1067–1073